(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
In the age of the Anthropocene, climate change has become a problematic issue full of undelayable challenges, both for the food system governance and their effects on public health. The main aim of this paper is to define terms and conceptualise the dual connection between climate and food; secondly, its purpose is to intercept the potential climate change effects on food security four dimensions: availability, accessibility, utilization and stability of food resources; furthermore, it aims to highlight the functional relevance of the holistic One Health approach in order to assess its opportunities for transformation and improvement of food sustainability. The final goal is to unhide that this perspective represents a prolific path for the preparation of effective regulatory and policy strategies, in line with the emerging mitigation paradigm.